Surgical Managment of Intracranial Invasive Aspergillosis in Immunocompetent Patients: Results from 3 Case Reports - K Quenum; L Rifi; M Boutarbouch; Y Arkha; S Derraz; A El Ouahabi; A Khamlichi (Journal of Neurological Research And Therapy, 2017)
Cerebral aspergillosis is a severe disease most commonly suspected in immunodeficient patients. The objective of this study is to determine the role of surgery in management of intracranial aspergillosis. We report three cases of immunocompetent patients presenting: posteriror fossa aspergillosis, sphenoidal extended to sellar region aspergillosis and post operative aspergillosis without extracerebral involvement. Microbiology and histological examination were carried out to provide the diagnosis. The patients underwent surgical procedure associated with medical treatment or not. In one case, surgical treatment was efficient. The outcome was good in two cases. Conclusion: Rapid diagnosis of invasive aspergillosis applying radiological and surgical procedures and immediate ignition of antifungal can be life saving.
Keywords: Invasive aspergillosis